Pemanfaatan Google Assistant dan Sistem Rekomendasi untuk Belajar Alkitab - David Kristian; Henry Novianus Palit; Leo Willyanto Santoso (Jurnal Infra, 2019)
There are several types of artificial intelligence that have been created by humans. Artificial intelligence is used to calculate, determine decisions, translate one language to another. In addition, various large technology companies such as Google and Apple have also created their own artificial intelligence, namely the Google Assistant and Siri. Of course the market segments of these two companies compete with each other, and so far Google Assistant which is more supportive of Android is more widely used than Siri.Google Assistant is an artificial intelligence that can help as a personal Assistant and integrated is in many ways with Smartwatch, Android Mobile, Google Home, car, TV, and others. Third-party developers can integrate their Apps with Google Assistant.This application uses Google Assistant, Dialogflow and Neo4j. This application helps study bible and see Biblical context better by using a recommendation system, and further the artificial Intelligence could make the conversation more natural. Users will be able to search various biblical data ranging from verse searches, outline verses, strong numbers, devotional, dictionaries about biblical data.